Generation of Neurosphere‐Derived Organoid‐Like‐Aggregates (NEDAS) from Neural Stem Cells. Issue 2 (3rd February 2021) - Watanabe, Fumihiro; Schoeffler, Austin; Fair, Summer R.; Hester, Mark E.; Fedorko, Josh; Imitola, Jaime
Abstract: Neurosphere cultures have been used to propagate and study the intrinsic properties of neural stem cells (NSCs) for more than two decades but this method has many limitations. It is well known that neurospheres fuse in culture, but the long‐term biological consequences of this phenomena are not well characterized. We leveraged the fusion behavior of human neurospheres to improve upon this technique with our Ne urosphere‐ d erived organoid‐like a ggregates (NEDAS) culture method, allowing the fusion of human NSCs at high density, which were maintained in orbital shaker conditions for 8‐12 weeks without passing leading to the formation of 3D organoid‐like aggregates without the use of Matrigel. NEDAS organoids proliferate and self‐organize into neural rosettes, expressing PAX6 and SOX2 in ventricular zone (VZ)‐like proliferative areas. Outside these rosettes, we identified corridors of migratory radial glial progenitors expressing Phospo‐vimentin, CRYAB. In addition to DLX2, CXCR4 + progenitors. Further, we found immature neurons within cortical‐like areas highly enriched for DCX and TUJ1, in addition to GABA+ and excitatory VGLUT1+ neurons. Here, we provide a protocol to generate NEDAS, additionally, we present a protocol for immunostaining of NEDAS organoids for confocal imaging. This protocol may be useful to dissect the self‐organization and morphogenetic programs of populations of human NSCs offering an advantageous alternative to the conventional neurospheres method, generating more cell type diversity, within tissue‐like aggregates over extended periods of time without dissociation or passing. NEDAS may be a complementary method to cerebral organoids protocols from IPSCs. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation and expansion of cultures of human neural stem cells in reduced growth factor basement matrix Basic Protocol 2 : Formation and fusion of neurospheres derived matrigel‐free organoid‐like aggregates (NEDAS) Basic Protocol 3 : Harvest, cryosection, and imaging protocol for NEDAS